Farah Antun: active reception of european thought - Puig Montada, Josep (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Farah Antûn (1874-1922) was a playwright and a journalist and in both activities he was socially and politically motivated. He always aimed at a laic state. In the beginning he believed it could comprise those lands of the Ottoman Empire from Istanbul to Cairo, later he focused in Egypt, although he may never have abandoned the first idea. He disseminated his ideas through his journal al-Jâmi´a. His social concerns shaped his views of such a state and its people. Farah Antûn read, translated, and explained European writers. His choices point to these concerns, namely on natural goodness and natural freedom (Bernardin de Saint-Pierre, Jean Jacques Rousseau), on religious freedom and freedom of conscience (Lev Tolstoy), on public instruction (Jules Simon). His ideal society should have an open approach to religion, inspired by A. Comte and, in particular, by E. Renan and his works, some of which he translated. His attitude toward Nietzsche was double-sided: He could not accept his moral doctrines but he felt attracted by his doctrine of power of will that supposedly had brought the United States to their magnificence and that could help the Arab countries to reach a new age. However those values as represented by the French liberal tradition were more decisive.
Keywords: Farah Antûn (1874-1922); journal al-Jâmi´a; «League»; modern translations into Arabic